2013
DOI: 10.1021/tx400284r
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Events Induced by Maleimides on Human Acute Leukemia Cell Lines

Abstract: Cyclic imides are known for their antitumor activity, especially the naphthalimide derivatives, such as Mitonafide and Amonafide. Recently, we have demonstrated the cytotoxic effect of a series of naphthalimide derivatives against B16F10 melanoma cells. On the basis of this fact, we have developed a study starting from the synthesis of different cyclic imides and the evaluation of their cytotoxic properties on human acute leukemia cells (K562 and Jurkat). Initially, a screening test was conducted to select the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…It was demonstrated that naphthalimides and maleimides activated the mitochondrial apoptotic pathway by changing the mitochondrial potential, increasing the level of the AIF and pro-apoptotic Bax proteins, and decreasing the level of anti-apoptotic proteins Bcl-2 and survivin [10,24]. On the other hand, maleimides activated the receptor apoptotic pathway by increasing the level of the membrane Fas receptor in Jurkat cells [25]. The profiles of gene expression (Figure 4) were similar to control experiment, where the cells were treated with staurosporine.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that naphthalimides and maleimides activated the mitochondrial apoptotic pathway by changing the mitochondrial potential, increasing the level of the AIF and pro-apoptotic Bax proteins, and decreasing the level of anti-apoptotic proteins Bcl-2 and survivin [10,24]. On the other hand, maleimides activated the receptor apoptotic pathway by increasing the level of the membrane Fas receptor in Jurkat cells [25]. The profiles of gene expression (Figure 4) were similar to control experiment, where the cells were treated with staurosporine.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that maleimides presented a good cytotoxic effect on human acute leukemia cells—K562 and Jurkat. [ 37 ] The results of cell cycle analysis, fluorescence microscopy, and Annexin V‐FITC assay confirmed that the cells were undergoing apoptosis after incubation with these compounds. The apoptosis induced by maleimides involved the intrinsic pathway, which was evidenced by the increased level of expression of pro‐apoptotic proteins Bax and AIF and the decreased level of expression of anti‐apoptotic protein Bcl‐2, and the extrinsic pathway only for Jurkat cells, evidenced by the increased level of expression of Fas.…”
Section: Resultsmentioning
confidence: 82%
“…Some of these maleimides also caused a decrease in the level of expression of anti‐apoptotic protein survivin. [ 37 ] Moreover, the cytotoxic effect of 9‐ING‐41, a maleimide‐based ATP‐competitive small molecule glycogen synthase kinase‐3β (GSK‐3β) inhibitor, is well known. [ 15,16 ] Treatment with 9‐ING‐41 has shown antitumor effects in different human cancers, like neuroblastoma, B‐cell lymphoma, glioblastoma, ovarian, pancreatic, renal, and breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The research results of Natalia S. et al [24] showed that N-substituted maleimides affected biosynthesis of chitin and β (1,3) glucan, components of the fungal cell wall. Furthermore, Karina [25] believed that N-PMI could trigger the apoptosis of erythrocyte, tumor cells, etc. and showed obviously the characteristic behaviors of apoptosis via ow cytometry, uorescene microscopy and Annexin V-FITC assay.…”
Section: Introductionmentioning
confidence: 99%